Curriculum mapping in higher education: a case study and proposed content scope and sequence mapping tool - Arafeh, Sousan (Journal of Further and Higher Education, 2016)
Best practice in curriculum development and implementation requires that discipline-based standards or requirements embody both curricular and programme scopes and sequences. Ensuring these are present and aligned in course/programme content, activities and assessments to support student success requires formalised and systematised review and development processes. These processes are not always in play in higher education, however. Using a descriptive qualitative case study strategy, this article shares how policy outcomes within intermediate and superintendent certification, sixth-year and Ed.D. doctoral courses and programmes at a state university were reviewed, mapped and assessed using an evidence-based curriculum analysis model and tool that mapped standards and outcomes from course syllabus data. Strengths and weaknesses of this approach are discussed and it is suggested that the field might benefit from a curriculum mapping and analysis method that also considers content coverage. A Course-Level Content Scope and Sequence Mapping Tool, developed to map content scope and sequence alongside standards or outcomes mapping, is presented for consideration and testing. The ability to assess and improve curriculum is only as good as the conceptual frameworks, methods and tools available. This critical case study is one effort to advance the field by drawing attention to the importance of curricular content mapping. The study should be of interest to higher education staff, researchers and accreditors concerned with postsecondary programmes and their curricular scope and sequence coherence, quality and improvement. © 2015 UCU.
Keywords: Curriculum; content; content mapping; curricular content; curricular scope and sequence; curriculum mapping; curriculum mapping tool; dept.edl; educational leadership; higher education; policy; programme coherence